Baicalin Ameliorates Pancreatic Fibrosis by Inhibiting the Activation of Pancreatic Stellate Cells in Mice with Chronic Pancreatitis - Jianwei Fan; Lifang Duan; Nan Wu; Xiaofan Xu; Jiaqi Xin; Shengnan Jiang; Cheng Zhang; Hong Zhang; Hong Zhang (Frontiers Media S.A., 2021)
Pancreatic inflammation and fibrosis are typical pathological features in chronic pancreatitis (CP). Activated pancreatic stellate cells (PSCs) have been regarded as the core event in the development of pancreatic fibrosis and are considered to be the key target for treatment of CP. Baicalin (C21H18O11), the main chemical composition of Baikal skullcap in the traditional Chinese medicines Dachaihu decoction (DCHD) and Xiaochaihu decoction (XCHD), has shown significant effects in the treatment of pancreatic fibrosis in CP mice; however, whether baicalin can inhibit the activation of PSCs and its underlying mechanism remain unclear. In this study, the influence of baicalin on activated PSCs in vitro and in vivo was investigated, and the results showed that Baicalin could significantly ameliorate the degree of pancreatic inflammation and fibrosis, while decreasing the levels of alpha-smooth muscle actin (α-SMA), F4/80 (surface markers of mouse macrophages), nuclear factor kappa-B (NF-κB), monocyte chemotactic protein 1 (MCP-1), and collagen type I alpha 1 (COL1A1)in the pancreas. Moreover, NF-κB and α-SMA were co-expressed in the pancreas of CP mice. Baicalin treatment markedly reduced the expression of co-location of α-SMA and NF-κB. In vitro, the protein expression levels of transforming growth factor-β receptor 1 (TGF-βR1), phosphorylated TGF-β activated kinase 1 p-TAK 1, and NF-κBp65 in PSCs were all remarkably reduced after treatment with baicalin. In addition, baicalin could inhibit MCP-1 mRNA expression in supernatant of activated PSCs, as well as the excessive migration of macrophages. Taken together, our findings indicated that baicalin could inhibit the TGF-β1/TGF-βR1/TAK1/NF-κB signaling pathway of activated PSCs, reduce the secretion of MCP-1, and further decrease the infiltration of macrophages and inflammation cells of the local microenvironment of the pancreas. Thus, this study provides a reliable experimental basis for baicalin in the prevention and treatment of CP.